Synthesis and Photocatalytic Properties of One-Dimensional Composite - Nanowires - Qianqian Zhang; Baibiao Huang; Peng Wang; Xiaoyang Zhang; Xiaoyan Qin; zeyan wang (International Journal of Photoenergy)
One-dimensional composite - nanowires were successfully fabricated by a simple microwave-assistant hydrothermal method. The successful fabrication of one-dimensional - nanowires can only be realized at pH value range of 1–5 of the starting solution. The fabricated nanowires were characterized by X-ray powder diffraction (XRD), scanning electron microscope (SEM), transmission electron microscopy (TEM), UV-visible diffuse reflectance spectra (UV-Vis DRS), and photoluminescence (PL), respectively. The diameter of the nanowires varies from 30 to 100 nm; the length is a few micrometers. Methylene blue (MB) solutions were used to evaluate the visible light photocatalytic activities of the fabricated samples. Compared with , the fabricated - nanowires show enhanced efficiency in oxidization of MB under visible light.